PENERAPAN DISIPLIN BERSIH KUKU DENGAN METODE PEMERIKSAAN SECARA BERKALA DI RA ASSALIMIYAH - Basthina, Alifa; Aini, Aneu Qurota; Amanah, Astri Tsamrotul; Anjangsari, Dewi Lara; Rahmadina, Garosha Putri; Kamaliah, Lia; Nur, Luthfi (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2024)
The most rapid spread of disease occurs through hands and nails. If there is a lack of hygiene on the hands, it will greatly affect and contribute to disease in the body. The purpose of this study was to determine the efforts made by teachers and parents in maintaining nail hygiene in children. This research was conducted at RA Assalimiyah, Ciamis. The method used in this research is a qualitative method, which aims to understand the phenomenon of what is experienced by the research subject. Qualitative research emphasizes more on data collected not from questionnaires but from interviews, observations, and documentation. It was found that the application of nail inspection habituation by teachers to children was able to improve the quality of nail hygiene in children. The application of nail hygiene discipline to children in RA Assalimiyah runs optimally. This is indicated by the implementation of nail examination routine at school. Children already have an awareness of the importance of maintaining nail health and hygiene.